The Prague cemetery [compact disc, unabridged] - Eco, Umberto (Recorded Books, 2011)
19th-century Europe, from Turin to Prague to Paris, abounds with the ghastly and the mysterious. Conspiracies rule history. Jesuits plot against Freemasons, Italian priests are strangled with their own intestines. French criminals plan bombings by day and celebrate black masses by night. Every nation has its own secret service, perpetrating forgeries, plots, and massacres. From the unification of Italy to the Paris Commune to the Dreyfus Affair to the notorious forgery "The Protocols of the Elders of Zion", Europe is in tumult and everyone needs a scapegoat. But, what if, behind all these conspiracies both real and imagined, lay just one man? What if that evil genius created the most infamous document of all?